Phosphatidylserine flux into mitochondria unveiled by organelle‐targeted Escherichia coli phosphatidylserine synthase PssA. (30th December 2020) - Shiino, Hiroya; Furuta, Shiina; Kojima, Rieko; Kimura, Keisuke; Endo, Toshiya; Tamura, Yasushi
Abstract : Most phospholipids are synthesised in the endoplasmic reticulum and distributed to other cellular membranes. Although the vesicle transport contributes to the phospholipid distribution among the endomembrane system, exactly how phospholipids are transported to, from and between mitochondrial membranes remains unclear. To gain insights into phospholipid transport routes into mitochondria, we expressed the Escherichia coli phosphatidylserine (PS) synthase PssA in various membrane compartments with distinct membrane topologies in yeast cells lacking a sole PS synthase (Cho1). Interestingly, PssA could complement loss of Cho1 when targeted to the endoplasmic reticulum (ER), peroxisome, or lipid droplet membranes. Synthesised PS could be converted to phosphatidylethanolamine (PE) by Psd1, the mitochondrial PS decarboxylase, suggesting that phospholipids synthesised in the peroxisomes and low doses (LDs) can efficiently reach mitochondria. Furthermore, we found that PssA which has been integrated into the mitochondrial inner membrane (MIM) from the matrix side could partially complement the loss of Cho1. The PS synthesised in the MIM was also converted to PE, indicating that PS flops across the MIM to become PE. These findings expand our understanding of the intracellular phospholipid transport routes via mitochondria. Abstract : How phospholipids travel among cellular membranes is a fundamental question in cell biology. Shiino et al . tackle this issue by expressing the Escherichia coli phosphatidylserine (PS) synthase PssA in various membrane compartments with distinct membrane topologies in yeast cells lacking a sole PS synthase. The synthesised PS can be converted to phosphatidylethanolamine by Psd1, the mitochondrial PS decarboxylase in mitochondria, suggesting the existence of previously overlooked phospholipid transport routes into mitochondria.